Case study on the benefits and risks of green hydrogen production co-location at offshore wind farms. Issue 4 (1st May 2022) - He, Wei; Zheng, Yi; You, Shi; Strbac, Goran; Therkildsen, Kasper T.; Olsen, Gudmund P.; Howie, Aaron; Byklum, Eirik; Sharifabadi, Kamran T.
Abstract: Abstract Advances in large-scale green hydrogen production (LGHP) create commercial opportunities for enhancing rapid offshore wind farm (OWF) development. This study investigates whether LGHP co-location at OWF sites improves those OWF's economic outlooks under potential electrical grid capacity bottlenecks towards 2050. Eight cases have been studied using measured annual OWF power production series and cost estimation integrated with offshore engineering experience: i) two base cases: 2 GW OWFs with HVAC and HVDC transmission infrastructure showing that the levelized cost of electricity (LCOE) increases, and ii) six LGHP co-location cases demonstrating that the calculated levelized cost of hydrogen (LCOH) reduces when the LGHP capacity increases from 20% to 50%, and 100% of 2 GW. Furthermore, three economic improvement factors studied are: i) utilizing existing gas pipelines reducing LCOH by 7.5%, ii) hydrogen for offshore customers changing "no-go" projects to "go", and iii) scaling-up from 2 to 4 GW reduced the LCOH by 17%. This study shows that LGHP co-location is effective at maintaining OWF full production, but has higher risks including i) LGHP co-location safety at OWFs, ii) high costs to cover more operational conditions and iii) running LGHP operations using high, fluctuating OWF power. Further R&D of LGHP co-location are recommended.